العروض العامة للشراء في سوق الأوراق المالية وأثرها على الأداء المالي للمؤسسة الاقتصادية – دراسة حالة السوق المالي السعودي - أحمد أمين جفافلية; نور الهدى سوايد (My University, 2022)
This study aims to answer the main problem related to the impact of public purchase offers on the financial performance in the Saudi financial market. First, shedding light on the financial performance and the factors affecting it, knowing the concept of the financial market, its types, and the parties involved. In addition to highlighting the most critical securities traded in the Financial market in general. Exploring the concept of public offers for purchase and its importance for the concerned parties, in addition to looking at the Saudi financial market. Public procurement is based on a group of references and research that dealt with the same subject in one way or another to answer the problem related to the impact of public offers for purchase on the financial performance in the stock market. Moreover, a case study approach was adopted on the Saudi financial market as it is a leading market in the Arab region that relies to a large extent on the circulation of public offers for purchase. The findings were as follows: a buy-out offer is a type of public takeover offer that allows any person to buy some or all of the shareholders’ shares in a company. Shares at a specified price and within a period of time-specific time. Public bids are one of the legal processes by which the ownership of the shares of the target company is transferred from the shareholders who own it to the offeror. This matter can lead to troubled restructuring companies through the offeror’s financing of these projects and helping them restore their activity. Offers to buy shares allow the offeror to achieve financial goals when he seeks to invest the shares he obtained in the offer framework by buying and selling these shares at a later time, in the process of taking advantage of the difference between the purchase price and the sale price. Public offer to purchase shares provides funding for restructuring companies facing financial difficulties because of a deficiency in funding or defective management. Furthermore, Adopting this system provides opportunities for restoring their activity and growth, purifying their management, and turning them into active companies that achieve profits or increase their profitability. ..................................................... نهدف من خلال هذه الدراسة الاجابة على الاشكالية الرئيسية المتعلقة بتأثير العروض العامة للشراء على الأداء المالي في السوق المالي السعودي، من خلال تسليط الضوء على الأداء المالي والعوامل المؤثرة فيه، معرفة مفهوم السوق المالي والأطراف المتدخلة فيه، تسليط الضوء على الأوراق المتداولة في السوق المالي عموما، معرفة المقصود بالعروض العامة للشراء واهميتها بالنسبة للأطراف المعنية اضافة الى القاء نظرة حول السوق المالي السعودي، حيث اعتمدنا في اعداد هذه الدراسة على نوعين من المناهج العلمية، المنهج الوصفي وذلك من خلال وصف متغيرات الدراسة الأداء المالي، السوق المالي، المنتجات المالية والعروض العامة للشراء بالاعتماد على مجموعة من المراجع و الأبحاث التي تطرقت لذات الموضوع بشكل او بأخر قصد الإجابة على الإشكالية المتعلقة بأثر العر وض العامة للشراء على الأداء المالي في سوق الأوراق المالية. ومنهج دراسة حالة حيث اعتمدنا على منهج دراسة الحالة في اعداد الجانب الميداني بالتطبيق على حالة السوق المالي السعودي باعتباره سوق رائد في المنطقة العربية يعتمد بدرجة كبيرة على تداول العروض العامة للشراء فيه. وتتمثل النتائج التي توصلنا اليها من خلال هذه الدراسة عرض الشراء من عروض الاستحواذ العامة التي تتيح لأي شخص شراء بعض نو كل نسه المساهمين في شركة ما، وعادة ما يت تقديم عروض الشراء علنا، ودعوة المساهمين لبيع اسهمه بسعر محدد وضمن فترة زمنية معينة. العروض العامة للشراء هي احدى العمليات التي بموجبها تنقل ملكية الشركة المستهدفة من المساهمين المالكين لها إلى صاحب العرض، وهذا الأمر يمكنه من ان يؤدي إلى إعادة هيكلة الشركات المتعثرة من خلال قيام صاحب العرض بتمويل هذه المشروعات ومساعدتها على استعادة وقارها. عروض شراء الأسهم تسمح لصاحب العرض تحقيق اهداف مالية عندما يسعى إلى استثمار الأسهم التي حصل عليها في إطار العرض، من خلال شراء هذه الأسهم وبيعها بعد مدة زمنية معينة وتحقيق ارباح من عائد البيع، مستفيدا بذلك من الفرق ما بين الثمن الذي اشترى به ومن البيع. وظام عروض شراء الأسهم له دور في إعادة هيكلة الشركات التي تعاني من قصور في التمويل خلل في الإدارة، تمويل هذه الشركات ومساعدتها على استعادة وشارها ونموها وتطهير الإدارة فيها، ومن ثم تحويلها إلى شركات ونشطة تحقق ارباح و تزيد من ربحيتها.